Immunohistochemical Characteristics of IgG4-Related Tubulointerstitial Nephritis: Detailed Analysis of 20 Japanese Cases. (31st July 2012) - Kawano, Mitsuhiro; Mizushima, Ichiro; Yamaguchi, Yutaka; Imai, Naofumi; Nakashima, Hitoshi; Nishi, Shinichi; Hisano, Satoshi; Yamanaka, Nobuaki; Yamamoto, Motohisa; Takahashi, Hiroki; Umehara, Hisanori; Saito, Takao; et al.
Abstract : Although tubulointerstitial nephritis with IgG4+ plasma cell (PC) infiltration is a hallmark of IgG4-related kidney disease (IgG4-RKD), only a few studies are available about the minimum number of IgG4+ PC needed for diagnosis along with IgG4+/IgG+ PC ratio in the kidney. In addition, the significance of the deposition of IgG or complement as a reflection of humoral immunity involvement is still uncertain. In this study, we analyzed 20 Japanese patients with IgG4-RKD to evaluate the number of IgG4+ PCs along with IgG4+/IgG+ PC ratio and involvement of humoral immunity. The average number of IgG4+ PCs was 43.8/hpf and the average IgG4+/IgG+ or IgG4+/CD138+ ratio was 53%. IgG and C3 granular deposits on the tubular basement membrane (TBM) were detected by immunofluorescence microscopy in 13% and 47% of patients, respectively. Nine patients had a variety of glomerular lesions, and 7 of them had immunoglobulin or complement deposition in the glomerulus. In conclusion, we confirmed that infiltrating IgG4+ PCs > 10/hpf and/or IgG4/IgG (CD138)+ PCs > 40% was appropriate as an item of the diagnostic criteria for IgG4-RKD. A relatively high frequency of diverse glomerular lesions with immunoglobulin or complement deposits and deposits in TBM may be evidence of immune complex involvement in IgG4-related disease.